Sex Proportionality in Pre-clinical and Clinical Trials: An Evaluation of 22 Marketing Authorization Application Dossiers Submitted to the European Medicines Agency - Dekker, Marieke J. H. J.; de Vries, Sieta T.; Versantvoort, Carolien H. M.; Drost-van Velze, Ellen G. E.; Bhatt, Mansi; van Meer, Peter J. K.; Havinga, Ineke K.; Gispen-de Wied, Christine C.; Mol, Peter G. M. (Frontiers in Medicine, 2021)
This study assessed to what extent women were included in all phases of drug development; whether the clinical studies in the marketing authorization application dossiers include information per sex; and explored whether there are differences between women and men in the drugs’ efficacy and safety. Data were extracted from dossiers submitted to the European Medicines Agency. Twenty-two dossiers of drugs approved between 2011-2015 for the treatment of various diseases were included. Female animals were included in only 9% of the pharmacodynamics studies but female and male animals were included in all toxicology studies. Although fewer women than men were included in the clinical studies used to evaluate PK (29% to 40% women), all dossiers contained sex-specific PK parameter estimations. In the phase III trials, inclusion of women was proportional to disease prevalence for depression, epilepsy, thrombosis, and diabetes (participation to prevalence ratio (PPR) range: 0.91-1.04), but women were considered underrepresented for schizophrenia, hepatitis C, hypercholesterolemia, HIV, and heart failure (PPR range: 0.49-0.74). All dossiers contained sex-specific subgroup analyses of efficacy and safety. There seemed to be higher efficacy for women in one dossier and a trend towards lower efficacy in another dossier. More women had adverse events in both treatment (73.0% versus 70.6%, P<0.001) and placebo groups (69.5% versus 65.5%, p<0.001). In conclusion, women were included throughout all phases of clinical drug research and sex-specific information is available in the evaluated dossiers. The included number of women is, however, not always proportional to disease prevalence rates.